Financial Sector Development, Economic Growth, and Poverty Reduction: A Literature Review - Juzhong Zhuang; Herath Gunatilake; Yoko Niimi; Muhammad Ehsan Khan; Yi Jiang; Rana Hasan; Niny Khor; Anneli S. Lagman-Martin; Pamela Bracey; Biao Huang (Asian Development Bank (ADB), 2009)
This paper reviews the theoretical and empirical literature on the role of financial sector development, with a view to deepening understanding of the rationale of development assistance to the financial sector of developing countries. The review leads to the following broad conclusions: (i) there are convincing arguments that financial sector development plays a vital role in facilitating economic growth and poverty reduction, and these arguments are supported by overwhelming empirical evidence from both cross-country and countryspecific studies; (ii) there are however disagreements over how financial sector development should be sequenced in developing countries, particularly the relative importance of domestic banks and capital markets and, in developing the banking sector, the relative importance of large and small banks; (iii) while broadening the access to finance by microenterprises, small and medium-sized enterprises (SMEs), and vulnerable groups is recognized as critically important for poverty reduction, it is also widely believed that microfinance and SME credit programs need to be well designed and targeted to be effective. In particular, these programs need to be accompanied by other support services such as provision of training and capacity building, assistance in accessing markets and technologies, and addressing other market failures; and (iv) financial sector development and innovation will bring risks, and it is therefore essential to maintain sound macroeconomic management, put in place effective regulatory and supervisory mechanisms, and carry out structural reforms in developing the financial sector. The paper argues that these conclusions provide a strong justification for development assistance to target financial sector development as a priority area, and that, like any public sector intervention, such assistance should be designed to address market and nonmarket failures. The paper also highlights several areas where more research is urgently needed, in particular, how to sequence financial sector development, how to balance the need for financial innovation and that for economic and financial stability, and how to make microfinance and SME credit programs work better to reduce poverty.
hdl:11540/1829
Keywords: 330